PENGARUH KOMBINASI EKSTRAK ETANOL DAUN SIRSAK (Annona Muricata L.) DAN SIMVASTATIN TERHADAP KADAR KOLESTEROL TOTAL DAN LOW DENSITY LIPOPROTEIN (LDL) TIKUS YANG DIINDUKSI PAKAN TINGGI LEMAK - Ririn Lispita Wulandari; Sri Susilowati; Murnik Asih (Universitas Wahid Hasyim Semarang, 2015)
ABSTRACT Soursop leaves can be used as a drug hypercholesterolemia. Simvastatin is one of the drugs that can be used to lower total cholesterol and LDL. This study aims to determine the effectiveness of combination therapy EEDS and simvastatin in inhibiting elevated levels of total cholesterol and LDL induced rats a high-fat feed when compared with simvastatin alone or single EEDS. This study is experimental with post-test only control group design. Using the test animals were 30 male rats Wistar strain were divided into 6 groups. Test animals fed a high-fat twice daily for 14 days except for the normal control group, the test preparation administration once a day for 5 days. Measurement of total cholesterol using the reagent kit CHOD-PAP and LDL measurement method Direct Enzymatic Colorimetric Test with a spectrophotometer UV-Visibel. Data were statistically analyzed by One Way Anova followed by Tukey test. The results showed that administration of EEDS can inhibit LDL levels induced rats a high-fat feed. eeds combination and simvastatin can inhibit the increase in total and LDL cholesterol levels did not differ significan (p> 0.05), which means it has the same ability in lowering total cholesterol and LDL induced rats a high-fat feed simvastatin compared with administration of single and single EEDS. Keywords: Hypercholesterolemia, Soursop Leaf Extract Ethanol, Total Cholesterol, LDL.